Application of Range of Motion in Stroke Patients with Impaired Physical Mobility - Suprapto Suprapto; Trimaya Cahya Mulat; A. Syamsinar Asmi; Muridah Muridah (Jurnal Edukasi Ilmiah Kesehatan, 2023)
Stroke is one of the serious diseases and can cause impaired physical mobility in patients. This impaired physical mobility can negatively impact the patient's daily life, including the ability to walk, stand, or perform other physical activities. The study aims to find out how the application of a range of motion in stroke patients with impaired physical mobility. Descriptive qualitative research design with a case study approach. The results of the application of passive ROM techniques carried out on non-hemorrhagic stroke patients with weaknesses in extremities are effective and ineffective, this is because the first patient and family are very enthusiastic and eager to move independently while the second patient and family lack motivation and surrender to the disease. It can be concluded that the response of the two patients is different due to the psychological factors of the patient and the family's understanding of the range of motion exercise given